A special coarsening mechanism for intergranular helium bubbles upon heating: A combined experimental and numerical study. (1st April 2018) - Gao, Jie; Huang, Hefei; Liu, Xiang; Wang, Chengbin; Stubbins, James F.; Li, Yan
Abstract: Here, by using in situ transmission electron microcopy, we discovered a special mechanism governing the coarsening of intergranular helium bubbles, which exhibit pancake-like growth along grain boundaries to achieve coalescence with another bubble upon heating at 673 K. The developed analytical model, addressing the stress field induced by the bubble internal pressure, well reproduced the observed shape evolution during the bubble growth. Moreover, we show that the coalescing rate of intergranular bubbles was controlled by the surface diffusion and can be accelerated by the pressure gradient between bubbles. Graphical abstract: A new coarsening mechanism of "Deformation and Coalescence" for intergranular helium nanobubbles upon heating at 673 K. Image 2